2006
DOI: 10.1016/j.brainres.2006.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chloride flux modulators in an in vitro model of brain edema formation

Abstract: Brain edema is a serious consequence of hemispheric stroke and traumatic brain injury and contributes significantly to patient mortality. In the present study, we measured water contents in hippocampal slices as an in vitro-model of edema formation. Excitotoxic conditions induced by Nmethyl-D-aspartate (NMDA, 300 μM), as well as ischemia induced by oxygen-glucose deprivation (OGD) caused cellular edema formation as indicated by an increase of slice water contents. In the presence of furosemide, an inhibitor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…It is widely accepted that NKCC plays an important role in cerebral edema formation after ischemia (Chen and Sun, 2005, Kumar et al, 2006). NKCC can be activated by decreasing pHi and contributes to acidosis-induced cytotoxic brain edema (Ringel et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that NKCC plays an important role in cerebral edema formation after ischemia (Chen and Sun, 2005, Kumar et al, 2006). NKCC can be activated by decreasing pHi and contributes to acidosis-induced cytotoxic brain edema (Ringel et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that permanent MCAO (24 h) creates predictable neuronal injury that is caused by both cytotoxic and vasogenic edema (Kumar et al, 2006;Mdzinarishvili et al, 2007). The brains were quickly removed and sectioned coronally into slices of 1 mm thickness using McIlwain Tissue Chopper.…”
Section: Methodsmentioning
confidence: 99%
“…* P < 0.01 versus vehicle-treated WT. AQP4 expression is attenuated with bumetanide treatment in WT but not in a-syn -/-mice cerebral edema [40,41]. Previous in vitro studies have suggested that furosemide was only effective in inhibiting water permeability in AQP4 channels when administered intracellularly [39].…”
Section: Discussionmentioning
confidence: 96%